Nurturing Healthy Media Consumption Habits in Early Childhood: A Social Campaign Approach - Lukitowati, Suci; Hanum, Aliyah Nur’aini; Yuliono, Agus (Universitas Ahmad Dahlan, 2023)
In contemporary society, the pervasive presence of digital devices has profoundly influenced the media consumption patterns of young children, presenting challenges and opportunities for their development. This study explores the impact of media content on early childhood and the urgent need for informed parental supervision. Utilizing a Research and Development (R&D) methodology, a comprehensive social campaign titled